Structurally Constrained Controllers Analysis and Synthesis - Sojoudi, Somayeh. (Springer US : Imprint: Springer, 2011)
Structurally Constrained Controllers: Analysis and Synthesis studies the control of interconnected systems, with a particular emphasis placed on networks, power systems and flight formations, to name just a few. This volume introduces four important problems regarding the control of such systems, and then proposes emerging techniques for solving them and insuring optimum system operation. This book also: Explains and investigates recent cutting edge applications including such topics as formation flying Offers complete coverage of robust control in structurally constrained controllers Discusses the performance evaluation of decentralized controllers Shows how to use new LMI method to solve traditional constrained control problems Structurally Constrained Controllers: Analysis and Synthesis is a must-read book for researchers and engineers working in the control field.